Nurses’ Job Satisfaction Regarding the Use of Health Technology: A Survey Study - Diah Arruum; Setyowati; Hanny Handiyani; Raldi Artono Koestoer (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
The development of innovative health technology is continuously needed by health workers, including nurses in hospitals. Nurses need to adapt and are required to be able to use various current technological innovations. However, the demand for quality care in maintaining patient safety through the use of technology is still an issue, thereby affecting the achievement of nurse job satisfaction. This study aims to describe the job satisfaction of nurses regarding the use of health technology. It is a descriptive study with a cross-sectional design that included 172 hospital nurses. The sample was selected using the purposive sampling method, and the data were collected through questionnaires. Of the nurses in the sample, 33.1% were between the ages of 26 and 31 years old, while 90.1% were female. Furthermore, regarding educational background, a majority of the nurses (54.1%) held diplomas in nursing, and 23.8% had professional nursing degrees. The maximum length of work experience taking care of patients was over 10 years. The results of this study showed that 40.1% of the nurses were satisfied with the use of health technology, while 59.9% were not satisfied. A significant relationship was found between education level, work position, and nurse satisfaction (p < 0.05). The recommendation of this study is that the manager’s role should include supporting, motivating, and providing self-awareness for the nurses regarding technology in order to save time, make communication more effective, facilitate nursing care, and improve patient safety. The manager should also be in charge of implementing easy-to-use technological innovations. Keywords: health technology, job satisfaction, nurse Abstrak Kepuasan Kerja Perawat melalui Pemanfaatan Teknologi Kesehatan: Sebuah Penelitian Survei. Perkembangan inovasi teknologi kesehatan terus dibutuhkan oleh tenaga kesehatan, termasuk perawat. Perawat perlu beradaptasi dan dituntut mampu menggunakan berbagai inovasi teknologi yang ada saat ini. Namun tuntutan terhadap kualitas pelayanan dalam menjaga keselamatan pasien melalui pemanfaatan teknologi masih menjadi isu sehingga memengaruhi pencapaian kepuasan kerja perawat. Penelitian ini bertujuan untuk mendeskripsikan kepuasan kerja perawat melalui pemanfaatan teknologi kesehatan. Penelitian ini merupakan penelitian deskriptif dengan desain cross-sectional yang mengobservasi melalui kuesioner pada 172 perawat rumah sakit, dipilih dengan menggunakan metode purposive sampling. Data yang dikumpulkan meliputi 33,1% perawat berusia antara 26-31 tahun, 90,1% adalah perempuan, 54,1% perawat berpendidikan diploma keperawatan, 23,1% adalah perawat professional. Lama bekerja maksimal 10 tahun lebih merawat pasien. Sebanyak 40,1% perawat merasa puas dengan penggunaan teknologi kesehatan, sedangkan 59,9% kurang puas. Analisis data menunjukan hubungan yang signifikan antara tingkat pendidikan, posisi kerja, dan kepuasan perawat (p < 0,05). Berdasarkan hasil penelitian, mayoritas perawat masih merasa tidak puas dengan penggunaan teknologi kesehatan. Peran perawat manajer ruangan seperti memberi dukungan, motivasi, dan edukasi dapat menumbuhkan kesadaran diri bagi perawat tentang manfaat teknologi untuk menghemat waktu, berkomunikasi yang lebih efektif, mendukung asuhan keperawatan, dan meningkatkan keselamatan pasien. Manajer juga bertugas menerapkan inovasi teknologi yang mudah digunakan. Kata Kunci: kepuasan kerja, perawat, teknologi kesehatan